KARAKTERISTIK PENDERITA LONG COVID - Luciana Tati Suparti; Maria Yunita Indriarini; Yosi Maria Wijaya (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
The COVID-19 disease is still unclear, including the long-term impact on its survivors. The further impact of survivors of COVID-19 or long covid is currently being studied by scientists worldwide. The phenomenon about the complaints of COVID-19 survivors that occurred during the pandemic varied greatly. The purpose of this study was to determine the characteristics of long covid sufferers which include various symptoms such as shortness of breath, fatigue, cough, headache, joint pain, muscle pain, difficulty thinking, anxiety, fever, stress, and chest palpitations. This research method is quantitative with descriptive design, where data collection using accidental sampling technique is obtained by 85 respondents participating in this study. This study used a questionnaire as a data collection tool and the data were analysed univariately by presenting the variable frequency distribution. The results showed that the number of patients with long covid symptoms who showed the most symptoms was fatigue (83.5%). The researcher suggests that further researchers examine the characteristics of other long covid and the direct impact on COVID-19 survivors with a larger population with different variables